2021
DOI: 10.2478/aoas-2020-0081
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic microorganisms and herbs in ruminant nutrition as natural modulators of health and production efficiency – a review

Abstract: Probiotics, prebiotics, synbiotics, direct-fed microbials, and herbs may improve the production efficiency in ruminants. The beneficial effect of selected specific microbes on animal health is reflected in protection against pathogens, stimulation of immunological response, increased production capacity, and mitigation of stress effects. Phytobiotic plants used in the nutrition of ruminant animals increase feed palatability. This in turn has a positive effect on feed intake and, consequently, increases product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 104 publications
0
8
0
Order By: Relevance
“…In ruminants, probiotics stimulate the reproduction, vital and metabolic activity of the ruminal microbiota, inhibit the development of pathogenic microbes in the digestive tract, exert immunomodulatory effects, and increase productive qualities of animals (Ogbuewu et al, 2018;Markowiak and Śliżewska, 2018;Bąkowski and Kiczorowska, 2021;Michalak et al, 2021;Vovk et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In ruminants, probiotics stimulate the reproduction, vital and metabolic activity of the ruminal microbiota, inhibit the development of pathogenic microbes in the digestive tract, exert immunomodulatory effects, and increase productive qualities of animals (Ogbuewu et al, 2018;Markowiak and Śliżewska, 2018;Bąkowski and Kiczorowska, 2021;Michalak et al, 2021;Vovk et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Many scientific experiments have shown that the use of fungal-based probiotics in the diet of ruminants stabilises the acidity of the rumen environment, activates microbial processes, stimulates the breakdown of fibre by ruminal microbiota, improves substrate supply to energetic and synthetic processes in tissues, as well as increases milk, meat and wool productivity of animals (Fuller, 1989;Newbold et al, 1996;Lee et al, 2003;Kutasi et al, 2004;Guedes et al, 2008;Desnoyers et al, 2009;Bąkowski and Kiczorowska, 2021;Michalak et al, 2021;Vovk et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The efficiency of digestion is linked to both animal genetics ( Brito et al, 2020 ) and characteristics of microbial ecosystem in the gut ( Kruger Ben Shabat et al, 2016 ). The function of microbiota can be improved by, e.g., optimizing the feeding or adding feed supplements ( Beauchemin et al, 2020 ; Erickson and Kalscheur, 2020 ), by modulating the microbial communities with antimicrobials or pro-and prebiotics ( Cameron and McAllister, 2016 ; Bąkowski and Kiczorowska, 2021 ). However, the fully established gut microbiota is resistant to changes, and often reverts to pre-manipulation state shortly after the end of the treatment ( Weimer, 2015 ; Weimer et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%